A tale of two cities: is air pollution improving in Paris and London?. (June 2019) - Font, Anna; Guiseppin, Lionel; Blangiardo, Marta; Ghersi, Véronique; Fuller, Gary W.
Abstract: Paris and London are Europe's two megacities and both experience poor air quality with systemic breaches of the NO2 limit value. Policy initiatives have been taken to address this: some European-wide (e.g. Euro emission standards); others local (e.g. Low Emission Zone, LEZ). Trends in NOX, NO2 and particulate matter (PM10, PM2.5 ) for 2005–2016 in background and roadside locations; and trends in traffic increments were calculated in both cities to address their impact. Trends in traffic counts and the distribution in Euro standards for diesel vehicles were also evaluated. Linear-mixed effect models were built to determine the main determinants of traffic concentrations. There was an overall increase in roadside NO2 in 2005–2009 in both cities followed by a decrease of ∼5% year −1 from 2010. Downward trends were associated with the introduction of Euro V heavy vehicles. Despite NO2 decreasing, at current rates, roads will need 20 (Paris) and 193 years (London) to achieve the European Limit Value (40 μg m −3 annual mean). Euro 5 light diesel vehicles were associated with the decrease in roadside PM10 . An increase in motorcycles in London since 2010 contributed to the lack of significant trend in PM2.5 roadside increment in 2010–16. Graphical abstract: Image 1 Highlights: NO2 and PM concentrations from traffic decreased from 2010–16 in Paris and London. Euro V diesel heavy vehicles induced downward trends in roadside NO2 . Effective reduction in traffic PM10 concentrations with of Euro 5 diesel lights. London observed faster decrease on PM10 concentrations from traffic than Paris. An increase in motorcycles in London caused higher roadside PM2.5 concentrations. Abstract : Trends in air pollutants in Europe's megacities.